Children in Greenland: disease patterns and contacts to the health care system. Issue 1 (1st January 2016) - Kløvgaard, Marius; Nielsen, Nina Odgaard; Sørensen, Thomas Lund; Bjerregaard, Peter; Olsen, Britta; Christesen, Henrik Thybo
Abstract : Background: Previous studies of Greenlandic children's disease pattern and contacts to the health care system are sparse and have focused on the primary health care sector. Objective: We aimed to identify the disease pattern and use of health care facilities of children aged 0–10 in two Greenlandic cohorts. Methods and design: In a retrospective, descriptive follow-up of the Ivaaq (The Greenland Child Cohort) and the CLEAR (climate changes, environmental contaminants and reproductive health) birth cohorts (total n=1, 000), we reviewed medical records of children aged 6–10 in 2012 with residence in Nuuk or Ilulissat (n=332). Data on diseases and health care system contacts were extracted. Diagnoses were validated retrospectively. Primary health care contacts were reviewed for a random sample of 1:6. Results: In 311 children with valid social security number, the total number of health care system contacts was 12, 471 equalling 4.6 contacts per child per year. The annual incidence rate of hospital admissions was 1:10 children (total n=266, 1, 220 days, 4.6 days/admission), outpatient contacts 2:10 children and primary care 3.6 per child. Contacts were overall more frequent in boys compared with girls, 39.5 versus 34.6 during the study period, p=0.02. The highest annual contact rates for diseases were: hospitalisations/acute respiratory diseases 13.9:1, 000; outpatient contacts/otitis media 5.1:1, 000; primary care/conjunctivitis or nasopharyngitis 410:1, 000 children. Outpatient screening for respiratory tuberculosis accounted 6.2:1, 000, primary care non-disease (Z-diagnosis) 2, 081:1, 000 annually. Complete adherence to the child vaccination programme was seen in 40%, while 5% did not receive any vaccinations. Conclusions: In this first study of its kind, the health care contact pattern in Greenlandic children showed a relatively high hospitalisation rate and duration per admission, and a low primary health care contact rate. The overall contact rate and disease pattern resembled those in Denmark, except for tuberculosis screening. Adherence to the vaccination programme was low. These findings may be helpful for the organisation and dimensioning of the Greenlandic health care system for children.